Study protocol of a population-based cohort investigating Physical Activity, Sedentarism, lifestyles and Obesity in Spanish youth: the PASOS study. Issue 9 (23rd September 2020) - Gómez, Santiago Felipe; Homs, Clara; Wärnberg, Julia; Medrano, Maria; Gonzalez-Gross, Marcela; Gusi, Narcis; Aznar, Susana; Cascales, Elena Marín; González-Valeiro, Miguel; Serra-Majem, Lluis; Terrados, Nicolás; Tur, Josep A; et al.
Abstract : Introduction: Physical activity (PA) is essential to healthy mental and physical development in early life. However, the prevalence of physical inactivity, which is considered a key modifiable driver of childhood obesity, has reached alarming levels among European youth. There is a need to update the data for Spain, in order to establish if current measures are effective or new approaches are needed. Methods and analysis: We present the protocol for Physical Activity, Sedentarism, lifestyles and Obesity in Spanish youth (PASOS). This observational, nationally representative, multicentre study aims to determine the PA levels, sedentary behaviours and prevalence of physical inactivity (defined as <60 min of moderate to vigorous PA per day) in a representative sample of Spanish children and adolescents. The PASOS study has recruited a representative random sample of children and adolescents aged 8–16 years from 242 educational centres in the 17 'autonomous regions' into which Spain is divided. The aim is to include a total of 4508 youth participants and their families. Weight, height and waist circumference will be measured by standardised procedures. Adherence to the Mediterranean diet, quality of life, sleep duration, PA and sedentary behaviour are being measured by validated questionnaires. PA is measured by the Physical Activity Unit 7-item Screener. A representative subsample (10% of participants) was randomly selected to wear accelerometers for 9 days to obtain objective data on PA. Parents are asked about their educational level, time spent doing PA, diet quality, self-perceived stress, smoking habit, weight, height, their child's birth weight and if the child was breast fed. Ethics and dissemination: The study was approved by the Ethics Committee of the Fundació Sant Joan de Déu, Barcelona, Spain. Main findings of the study will be disseminated to the scientific community and to general public by media conferences, social media and a website. Trial registration number: ISRCTN34251612 .